Conceptualising the inspirational effect of elite sport: a case study of field hockey in Belgium. Issue 5 (20th October 2021) - de Cocq, Sebastiaan; Derom, Inge; Bosscher, Veerle De
ABSTRACT: Research question: This study aims to better understand and conceptualise the dynamics of inspirational elite sport. Specifically, taking Belgian hockey as a case study, this article is concerned with understanding how, why, and under what circumstances elite sport influences grassroots sport participation in voluntary sports clubs (i.e. trickle-down effect). Research methods: Fourteen semi-structured interviews were conducted with high-profile stakeholders who have been involved in the development of field hockey in Belgium. Results: The inspirational effect of elite sport is conceptualised through dynamic relationships between the properties of elite sport that act as drivers of inspiration and the engagement of stakeholders, that identified these drivers as catalysts for additional investments to strengthen elite sport. It is however imperative to fulfil preconditions at the grassroots level to realise potential outcomes of the inspirational effect on individuals' behaviour. Implications: If sport policy intends to deploy elite sport as a vehicle for increased sport participation in voluntary sport clubs (VSCs), properties of inspiring elite sport should be actively considered and managed with the engagement of intersectoral stakeholders with diverse interests. In addition to strengthening elite sports, policy instruments should be utilised to ensure that inspirational effects can occur in VSCs.